Performance Analysis of a Small-Scale Biogas-Based Trigeneration Plant: An Absorption Refrigeration System Integrated to an Externally Fired Microturbine - Villarroel Schneider, Jhonny (2019)
Trigeneration or combined cooling, heat and power (CCHP) systems fueled by raw biogas can be an interesting alternative for supplying electricity and thermal services in remote rural areas where biogas can be produced without requiring sophisticated equipment. In this sense, this study considers a performance analysis of a novel small-scale CCHP system where a biogas-fired, 5 kW el externally fired microturbine (EFMT), an absorption refrigeration system (ARS) and heat exchangers are integrated for supplying electricity, refrigeration and hot water demanded by Bolivian small dairy farms. The CCHP solution presents two cases, current and nominal states, in which experimental and design data of the EFMT performance were considered, respectively. The primary energy / exergy rate was used as a performance indicator. The proposed cases show better energy performances than those of reference fossil fuel-based energy solutions (where energy services are produced separately) allowing savings in primary energy utilization of up to 31%. Furthermore, improvements in electric efficiency of the EFMT and coefficient of performance (COP) of the ARS, identified as key variables of the system, allow primary energy savings of up to 37%. However, to achieve these values in real conditions, more research and development of the technologies involved is required, especially for the EFMT. (15) (PDF) Performance Analysis of a Small-Scale Biogas-Based Trigeneration Plant: An Absorption Refrigeration System Integrated to an Externally Fired Microturbine. Available from: https://www.researchgate.net/publication/336398032_Performance_Analysis_of_a_Small-Scale_Biogas-Based_Trigeneration_Plant_An_Absorption_Refrigeration_System_Integrated_to_an_Externally_Fired_Microturbine [accessed Nov 27 2019].